2020
DOI: 10.3390/biom10111555
|View full text |Cite
|
Sign up to set email alerts
|

Detention in Juvenile Correctional Facilities Is Associated with Higher Platelet Monoamine Oxidase B Activity in Males

Abstract: Juvenile delinquency is related to several biological factors, yet very few vulnerability biomarkers have been identified. Previous data suggest that the enzyme monoamine oxidase B (MAO-B) influences several personality traits linked to the propensity to engage in delinquent behavior. Building on this evidence, we assessed whether conduct disorder (CD), juvenile delinquency adjudications, or detention in a correctional facility were associated with either platelet MAO-B activity or the MAOB rs1799836 polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
1
1
Order By: Relevance
“…Compared with 27% severely agitated subjects [52] or 23% severely agitated veterans with PTSD [39] included in our previous studies, our study included less than 20% of severely agitated veterans with PTSD, and these results might suggest that severe excitement or agitation was not so frequent in this group of veterans with PTSD who were treatmentseeking and sampled in the hospital. In contrast to our results, higher platelet MAO-B activity was found in aggressive male youth living in juvenile detention, with or without conduct disorder; however, it was not associated with dissociative/aggressive/delinquent behavior, but only with the scores of verbal aggression, evaluated using the Overt Aggression Scale-Modified verbal aggression subscale [34]. On the other hand, lower platelet MAO-B activity was detected in incarcerated juvenile delinquents with high levels of novelty seeking, characterized by impulsivity, sensation seeking, and elevated exploratory activity [33], or in violent offenders from the prison [61].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Compared with 27% severely agitated subjects [52] or 23% severely agitated veterans with PTSD [39] included in our previous studies, our study included less than 20% of severely agitated veterans with PTSD, and these results might suggest that severe excitement or agitation was not so frequent in this group of veterans with PTSD who were treatmentseeking and sampled in the hospital. In contrast to our results, higher platelet MAO-B activity was found in aggressive male youth living in juvenile detention, with or without conduct disorder; however, it was not associated with dissociative/aggressive/delinquent behavior, but only with the scores of verbal aggression, evaluated using the Overt Aggression Scale-Modified verbal aggression subscale [34]. On the other hand, lower platelet MAO-B activity was detected in incarcerated juvenile delinquents with high levels of novelty seeking, characterized by impulsivity, sensation seeking, and elevated exploratory activity [33], or in violent offenders from the prison [61].…”
Section: Discussioncontrasting
confidence: 99%
“…Platelet MAO-B activity was reported to be reduced in different psychopathological and disinhibited, criminal, and violent behaviors and aggression [21,[30][31][32][33]. However, opposing data also exist [34,35]. Increased platelet MAO-B activity was found in aggressive male youth living in juvenile detention, which was not associated with delinquent behavior [34], or in adult male subjects with chronic alcohol dependence, which was not affected by alcohol-related phenotypes [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was assumed that the A allele of the MAO-B rs1799836 was associated with higher MAO-B activity [42,77] and, therefore, may result in lower subcortical dopamine levels. However, some studies reported higher enzyme activity in G allele carriers [78,79], while our previous studies reported no differences in platelet MAO-B activity in carriers of the A or G allele [80][81][82][83][84], questioning the hypothesis of its functionality. In addition, MAO-B rs1799836 was not found to be a functional polymorphism in a meta-analysis [19].…”
Section: Discussioncontrasting
confidence: 65%
“…This is in partial disagreement with the findings of higher affective flattening in Mexican women with schizophrenia who were G carriers, although this significance was lost after Bonferroni correction, while no differences were detected in other negative symptoms, including anhedonia [44]. The discrepancies may arise from the differences in age, smoking status and ethnic differences, which all affect MAO-B activity [81,84], but also from the effects of other polymorphisms inside the MAOB gene. For example, participants in the latter study were 10 years younger than our patients [44].…”
Section: Discussionmentioning
confidence: 64%